Precision nutrition impact on metabolic health and quality of life in aging population after a 3-month intervention: A randomized intervention - Cristina Galarregui; Santiago Navas-Carretero; M. Angeles Zulet; Carlos J. González-Navarro; J. Alfredo Martínez; Begoña de Cuevillas; Helena Marcos-Pasero; Elena Aguilar-Aguilar; Guillermo Reglero; Ana Ramirez de Molina; Paloma Chausa; Jose M. Iniesta; et al. (Elsevier, 2024)
Objectives: Innovative precision dietary procedures are required to promote healthy aging. This study aimed to evaluate the effects of a personalised strategy based on the inclusion of individualised foods and digital tools on overall health status and quality of life within a follow-up of 3 months in older adults with overweight or obesity. Methods: 127 men and women aged between 50 and 80 years with overweight/obesity participated in the study-between January 2020 and September 2020 at the Center for Nutrition Research-University of Navarra and IMDEA-ALIMENTACIÓN-and were randomly assigned to a usual-care group (standard recommendations) or precision group (precision nutrition strategy based on the inclusion of individualised foods and a mobile application). Anthropometry, body fat percentage, biochemical parameters, diet, and quality of life (SF-36 Health Survey) were assessed at baseline and after 3 months. Results: Both strategies were found to improve overall metabolic health; however, the precision approach demonstrated significantly better outcomes. The precision strategy reduced body weight at 3 months (−4.3 kg; p < 0.001) with significant improvements in body fat percentage, blood pressure and general metabolic health (glycated haemoglobin; alanine aminotransferase; aspartate aminotransferase; hepatic steatosis index) in comparison with the standard recommendations. The precision approach significantly enhanced the quality of life (SF-36) of individuals, with additional improvements in emotional well-being (p = 0.024) and vitality (p = 0.008). Adherence to the Mediterranean diet was significantly associated with a higher quality of life and vitality. Conclusion: These results support the benefit of precision nutrition approaches for promoting healthy aging and emotional well-being, enhancing the quality of life in aging populations, during the COVID-19 pandemic.